Oxidation Behavior of Zr-based Amorphous Alloys at 400˚- 450˚C in Air - Triwikantoro Triwikantoro; Romdhoni Graha Pribadi; Fatimatul Munawaroh (JURNAL PENA SAINS, 2019)
The study of oxidation behavior of amorphous alloys based on Zirconium with 2 variations in composition was carried out: Zr64.5Cu17Ni11Al7.5 and Zr69.5Cu12Ni11Al7.5 at temperatures of 400 - 450˚C in air. Amorphous Zr-based alloys were thermally characterized using Differential Scanning Calorimeter (DSC) to determine the crystallization temperature and glass transition temperature. The oxidation characterization was carried out using a Thermo gravimetric Analyzer (TGA) at temperatures of 400, 425, and 450˚C for 4 hours in air. The phase analysis of the oxidation product was identified using X-Ray Diffaction (XRD). Based on DSC data the crystallization temperature for Zr64.5Cu17Ni11Al7.5 and Zr69.5Cu12Ni11Al7.5 is 426 and 442˚C respectively. The oxidation kinetics of the two alloys follow parabolic law and the oxidation rate increases with the addition of temperature. Oxides formed during isothermal oxidation in the Zr64.5Cu17Ni11Al7.5 and Zr69.5Cu12Ni11Al7.5 alloys are t-ZrO2 (tetragonal) as the dominant phase and ZrO2 (monoclinic) and CuO as the minor phase. The intermetallic phase is also formed in both samples, t-Zr2Ni and Zr2Cu.